Following social norms, signaling, and cooperation in the public goods game - Cui, Chi; Dai, Ming; Schwieren, Christiane (AWI discussion paper series, 2024)
In this paper, we experimentally investigate how sending a signal of following social norms impacts people's cooperative behavior in a repeated public goods game, where we disentangle the effect of strategy and internalization of social norms on cooperation. We find that under the signaling mechanism, less cooperative players disguise themselves in the rule-following game, but this does not decrease cooperation overall. More importantly, the signaling mechanism has a heterogeneous effect on cooperation in rule-following and rule-breaking groups: It increases cooperation in rule-following groups but decreases cooperation in rule-breaking groups. Finally, the signaling mechanism tends to offset the decline of contributions among participants in rule-breaking groups rather than rulefollowing groups. Overall, this paper provides a feasible way to improve social cooperation and enriches the literature on cooperation in the public goods game.
Keywords: Graue Literatur